2015
DOI: 10.1007/s00405-015-3738-y
|View full text |Cite
|
Sign up to set email alerts
|

Malignant otitis externa in a healthy non-diabetic patient

Abstract: A healthy 60-year-old male was initially treated for external otitis, and subsequently received multiple surgeries including abscess drainage, temporal bone debridement, canaloplasty of the external auditory meatus, and fistula excision and was treated with numerous antibiotics at another hospital over a 1-year period. He was seen at our hospital on February 14, 2014 with a complaint of a non-healing wound behind the left ear and drainage of purulent fluid. He had no history of diabetes mellitus or compromised… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 7 publications
0
13
0
2
Order By: Relevance
“…Another previously described case of NOE complicated by cerebral abscess was successfully treated with extensive surgical debridement and abscess drainage, although this was in an older (60-year-old) patient with diabetes 9. Similarly, aggressive treatment was successful in a healthy 60-year-old man free of diabetes and immunocompromise who developed NOE complicated by epidural abscess 10…”
Section: Discussionmentioning
confidence: 99%
“…Another previously described case of NOE complicated by cerebral abscess was successfully treated with extensive surgical debridement and abscess drainage, although this was in an older (60-year-old) patient with diabetes 9. Similarly, aggressive treatment was successful in a healthy 60-year-old man free of diabetes and immunocompromise who developed NOE complicated by epidural abscess 10…”
Section: Discussionmentioning
confidence: 99%
“…Sami Horani, BS 1 , Shiva P. Daram, MD, MBA 2 , Gopi Shah, MD 3,4 , and Ron B. Mitchell, MD 3,4 A 11-year-old male presented to the hospital with a 2-day history of right otalgia, purulent otorrhea, and swelling after hot tub exposure. There was no significant medical, family, or social history.…”
Section: A Unique Case Of Malignant Otitis Externamentioning
confidence: 99%
“…3 However, there have been selective cases of MOE in immunocompetent adults. 4,5 Pseudomonas aeruginosa is causative in over 90% of cases, but Staphylococci, Streptococci, and gram-negative bacteria have also been implicated. 2,6 Recent studies on MOE have reported increased pathogen diversity.…”
Section: A Unique Case Of Malignant Otitis Externamentioning
confidence: 99%
“…Local treatment (with removal of bone sequestered) and treatment with systemic antibiotics conferring to the outcomes of bacteriological tests (aminoglycosides, semisynthetic penicillins, third-and fourth generation cephalosporins, fluoroquinolones) are usually accepted. 9 Principal treatment of MOE comprises management of pain, removal of debris in the external auditory canal (EAC), topical medication administration for controlling edema and infection and prevention of contributing aspects. Treatments of topical antimicrobials result in a higher cure rate than placebo, and preparations of corticosteroid lessen swelling, secretions and erythema.…”
Section: Introductionmentioning
confidence: 99%